Dynamic analysis of PVC gel actuators considering viscoelastic damping: Coupled electromechanical mechanism and nonlinear vibrational behavior - Yang Xiao; Bin Luo; Hanjing Lu; Xue Wen; Zhigang Chen (AIP Advances)
Polyvinyl chloride (PVC) gel is a kind of soft, intelligent material with high deformability. The stress effect after stimulation by electrical signals is similar to the phenomenon of biological muscle contraction. It has important application prospects in the development of flexible actuators and soft robots. However, the influence of viscoelasticity on the nonlinear dynamic behavior of the PVC gel actuator has not been explored. The viscous damping effect caused by the inherent viscoelasticity of PVC gel has a significant effect on the nonlinear dynamic behavior of PVC gel. In this study, considering the influence of viscous damping force on PVC gel, aiming at the electromechanical coupling mechanism of PVC gel actuator vibration, a nonlinear dynamic mathematical model of PVC gel actuator vibration combined with a viscous damping effect was established, and the numerical solution was obtained by the Runge–Kutta method. The dynamic responses of PVC gel actuators with and without damping were compared and analyzed. The results show that in the undamped state, harmonic resonance occurs in the PVC gel actuator; moreover, sub-harmonic resonance and super-harmonic resonance occur at the same time. In the case of damping, damping force, voltage amplitude, prestress, and ultimate tension have an effect on the vibration of the PVC gel actuator. The dynamic stability and periodicity of the PVC gel actuator were studied by means of phase paths, Poincaré maps, bifurcation, and Lyapunov exponent. At the same time, the resonance characteristics of the PVC gel actuator under various parameters were also analyzed. This study lays a theoretical foundation for the application of PVC gel in the field of flexible drive.